Mechanochemical Synthesis of p-Nitro Calix[6]arene - CHENNAKESAVULU, K.; BHASKAR RAJU, G. (Asian Journal of Chemistry, 2010)
A novel procedure was developed for the synthesis of p-nitro calix[6]arenes from p-tert-butyl calix[6]arene by mechanical activation. Mixture of p-tert-butyl calix[6]arene dissolved in dichloromethane, glacial acidic acid and anhydrous HNO3 was subjected to intense mechanical activation/agitation in planetary ball mill. The nitro substituted calix[6]arene with 97 % purity and 75 % yield was formed within 2.5 h which otherwise takes several hours to complete the reaction.